Roles of interferon and cellular adhesion molecules in bacterial activation of human natural killer cells - Lindemann, R A (Infection and immunity, 1989)
Interaction of lipopolysaccharide (LPS) from enteric and oral bacteria with natural killer (NK) cells enhanced cytotoxicity against NK-sensitive and NK-resistant targets. This activation occurred without expansion of the NK cell population or without changes in the leukocyte function-associated antigen family of cellular adhesion molecule (CAM) expression on NK cells. Significant interferon (IFN) titers were measured in LPS-lymphocyte supernatants, and antibody to IFN-alpha blocked LPS activation. LPS-induced NK cytotoxicity was inhibited by antibodies to individual alpha chains of CAM and, more profoundly, by antibody to the beta chain of CAM. However, LPS, when preincubated with NK cells, did not compete with subsequent anti-CAM antibody binding as detected by flow cytometry. Anti-CAM antibodies had no effect on NK activation by IFN, but antibodies to either CD11a or CD11c abrogated IFN production induced by LPS. These findings suggest that LPS binds NK cells at non-CAM sites, resulting in the release of IFN. IFN then acts in an autocrine manner independent of CAM to enhance NK cytotoxicity. Interaction of anti-CAM antibodies with CAM may provide a negative signal in regulating LPS-induced IFN production.